EKSPLORASI KEMAMPUAN MENULIS SISWA MELALUI PROGRAM MEMBACA DAN MENULIS CERDAS BERBASIS DESAIN JURNAL LITERASI - Rita Ratna Sari; Sri Endang; Suri Andani; Tri Rohana Wati; Aan Maulana; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Study aims to investigate the effectiveness of a literacy program that combines reading and writing activities through a literacy journal design in improving the writing skills of elementary school children. The study employed a qualitative, descriptive research method and was conducted at SDN 1 Cakranegara, involving 28 fifth-grade students and a teacher as an additional informant. Data were collected through observation, interviews, and document analysis, while data analysis followed the model proposed by Miles and Huberman. The findings indicate that a program focused on reading and writing using a literacy journal can significantly improve students’ writing skills, as evidenced by their ability to compose texts with a more organized structure, develop ideas, and use more appropriate vocabulary and language. Students became more confident in expressing their thoughts and reflections, and there was a noticeable increase in motivation and participation during the learning process. The literacy program based on a literacy journal has proven successful in improving writing skills while simultaneously fostering students’ literacy habits, making it a viable alternative as an innovative and effective learning strategy at the elementary school level.